Peter Rabbit and friends - Potter, Beatrix, 1866-1943 (Frederick Warne, an imprint of Penguin Random House LLC, 2020)
Revisit the timeless tales of Peter Rabbit, Benjamin Bunny, and more of their pals as they go on adventures, get into trouble, and learn valuable lessons. New readers and dedicated collectors alike will appreciate this Classic Gift Edition complete with Beatrix Potter's original treasured text and illustrations. Celebrate these unforgettable characters as they come to life once more!